The Role of Workload and Work Life Balance on Employee Performance at PT XYZ Yogyakarta - Primartono, Yoshua; Wahyudi, Idam; Nurmalasari, Auliya; Bikorin, Bikorin; Sulistyowati, Anggun (The Future of Education Journal, 2026)
This study is motivated by the importance of maintaining employee performance amid increasing work demands and the evolving dynamics of modern work patterns, particularly in digital service companies. High workload and an imbalance between work and personal life are considered key factors influencing employee performance. Therefore, this study aims to analyze the effect of workload and work life balance on employee performance at PT XYZ Yogyakarta. This research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to a total of 77 respondents. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects of the independent variables on employee performance. The results show that workload has a significant negative effect on employee performance, while work life balance has a significant positive effect. Simultaneously, both variables also have a positive and significant effect on employee performance. The coefficient of determination (R²) of 0.337 indicates that 33.7% of the variation in employee performance can be explained by workload and work life balance, while the remaining 66.3% is influenced by other factors outside the research model. This study implies that organizations need to manage workload proportionally and enhance employees’ work life balance to improve overall performance.